Groundnut Bud Necrosis Virus Modulates the Expression of Innate Immune, Endocytosis, and Cuticle Development-Associated Genes to Circulate and Propagate in Its Vector, Thrips palmi - Mahanta, Deepak Kumar; Jangra, Sumit; Priti,; Ghosh, Amalendu; Sharma, Parva Kumar; Iquebal, Mir Asif; Jaiswal, Sarika; Baranwal, Virendra Kumar; Kalia, Vinay Kumari; Chander, Subhas (Frontiers in Microbiology, 2022)
Thrips palmi (Thysanoptera: Thripidae) is the predominant tospovirus vector in Asia-Pacific region. It transmits economically damaging groundnut bud necrosis virus (GBNV, family Tospoviridae) in a persistent propagative manner. Thrips serve as the alternate host and virus reservoirs making tospovirus management very challenging. Insecticides and host plant resistance remain ineffective in managing thrips-tospovirus. Recent genomic approaches have led to understanding the molecular interactions of thrips-tospoviruses and identifying novel genetic targets. However, most of the studies are limited to Frankliniella species and tomato spotted wilt virus. Amidst the limited information available on T. palmi-tospovirus relationships, the present study is the first report of the transcriptome-wide response of T. palmi associated with GBNV infection. The differential expression analyses of the triplicate transcriptome of viruliferous vs non-viruliferous adult T. palmi identified a total of 2363 (1383 up and 980 downregulated) significant transcripts. The GO and KEGG Pathway enrichment analyses showed the abundance of DEGs involved in innate immune response, endocytosis, cuticle development, receptor binding and signaling that mediate the virus invasion and multiplication in the vector system. Also, the gene regulatory network of most significant DEGs showed the genes like ABC transporter, cytochrome P450, endocuticle structural glycoprotein, gamma-aminobutyric acid (GABA) receptor, heat shock protein 70, larval and pupal cuticle proteins, nephrin, proline-rich protein, sperm associated antigen, UHRF1-binding protein, serpin, tyrosine-protein kinase receptor, etc. were enriched with higher degrees of interactions. Further, the expression of the candidate genes in response to GBNV infection was validated in RT-qPCR. This study leads to an understanding of molecular interactions between T. palmi and GBNV and suggests potential genetic targets for generic pest control.